ENDOVASCULAR TREATMENT FOR CHRONIC CORONARY OCCLUSIONS IN PATIENTS WITH CORONARY HEART DISEASE - R. O. Shirokov; A. N. Samko; B. I. Milen’kin; E. V. Merkulov; I. V. Levitskiy; V. M. Mironov; A. S. Tereshchenko; S. I. Provatorov; Sh. T. Zhamgyrchiev; D. N. Filatov; A. M. Gerasimov (Вестник рентгенологии и радиологии)
Objective: to analyze the angiographic results of endovascular treatment for chronic coronary occlusions in patients with coronary heart disease.Material and methods. In 2009 to 2013 attempted endovascular recanalization of chronic coronary occlusions in 854 patients with coronary heart disease. The patients’ age ranged from 36 to 68 years (mean 52 years). The estimated duration of occlusion was 1 month to more than 3 years. There were 193 (22.6%) females and 661 (77.4%) males. 462 (54.1%) patients had a history of myocardial infarction. 738 (86.4%) and 116 (13.6%) patients had true (TIMI grade 0) and functional (TIMI grade 1) occlusions, respectively. Multi- and univascular lesions were found in 683 (79.9%) and 171 (20.1%) patients, respectively. Silent occlusions with preserved myocardial contractility were identified in 165 (19.3%) patients.Results. Blood flow could be successfully restored in 616 (72.1%) patients. Recanalization of chronic coronary occlusion failed in 238 (27.9%) patients.Conclusion. Recanalization of chronic coronary occlusions is a highly effective and relatively safe technique. The efficiency of the procedure largely depends on the duration of occlusion, its X-ray morphological characteristics, and the experience of a physician.